What Drives Generation Z to Purchase on Shopee: Digital Marketing, Pricing, or Online Reviews?(Study on Students of the Faculty of Economics and Business, UNNES) - Eriyani, Eriyani; Via Amalia (Universitas Negeri Semarang, 2025)
This study investigates the key determinants influencing Generation Z's purchase intention on Shopee, focusing on three main variables: digital marketing, pricing, and online reviews. The research was conducted among students from the Faculty of Economics and Business at Universitas Negeri Semarang (UNNES) using a quantitative approach. Data were collected through a structured questionnaire and analyzed using multiple linear regression. The findings reveal that both digital marketing and online reviews have a significant and positive impact on purchase intention. In contrast, pricing shows a significant but negative effect, indicating that Generation Z is highly price-sensitive and more influenced by perceived value and peer reviews. The model explains 68.0% of the variance in purchase intention (R² = 0.680), suggesting a strong relationship between the examined variables and consumer behavior. These results highlight the importance of authentic digital engagement and customer feedback in driving online purchases among young consumers. E-commerce platforms are advised to prioritize trust-building strategies and maintain price competitiveness to target the Gen Z segment effectively.